Gambaran Pengetahuan Gizi Mahasiswa Fakultas Kesehatan Masyarakat Universitas Islam Negeri Sumatera Utara - Al Fahri, Muhammad; Hasibuan, Sarah Adelia; Azzahra, Annisa Faradila; Silvia, Laila; Harahap, Putri Anggi Marshanda; Ananda, Annisa; Putri, Khairani; Wasiyem, Wasiyem (Innovative: Journal Of Social Science Research, 2025)
Nutritional status is an important factor in achieving optimal health. The level of nutritional knowledge in each individual will influence the individual in choosing food and consuming food that is appropriate, balanced, varied, and does not cause disease. The aim of this research is to determine the description of nutritional knowledge among students at the Faculty of Public Health, North Sumatra State Islamic University. This type of research is a Descriptive Survey carried out at the Faculty of Public Health, North Sumatra State Islamic University in December 2024-January 2025. The sample in this research was 198 students. Sampling used a saturated sampling technique. The measuring tool used was a questionnaire about nutritional knowledge online via Google Form. Data were analyzed using univariate analysis. The results of this study show that the description of nutritional knowledge of students at the Faculty of Public Health, North Sumatra State Islamic University, most of the respondents were at a sufficient level of knowledge, namely 130 people with a percentage value of 65.5%, and respondents at a good level of knowledge, namely 59 respondents with a percentage value. 29.8%, while only 9 respondents had less level of knowledge with a percentage value of 4.6%.